Factors influencing urban environmental sustainability actions─an investigation on urban public space in the study area. Issue 3 (2nd September 2021) - Chen, Ssu-Hsien
ABSTRACT: What are patterns, outcomes, and factors emerging from the urban environmental sustainability actions? To what extent do the conditions of action arenas facilitate urban environmental actions? In this research, the community-level public space named 'neighbourhood activity centres' in Taipei City is observed and investigated. Besides the field observation effort, a data set is established with the combination of subjective and objective data sources collected from a questionnaire investigation (255 units of observations) and the governmental open data systems. After employing ordinary least squares (OLS) regression analysis, the author concludes that environmental friendly facilities (such as aquaponics systems), environmental tendency of the communities, exhibition of policies or regulations and action networks among participants, could facilitate the outcomes of urban environmental sustainability movement. However, the diversity among the participants negatively affects the relationships between some external factors and action outcomes. The divergence in actor preference increases the required transaction costs in the consensus process due to time-consuming communication and compromise. This study thus proposes recommendations, such as benchmark Lis and neighbourhood associations, as policy application that could enhance municipal implementation of sustainability policies.